A quasi-experimental evaluation of dried blood spot testing through community pharmacies in the Tayside region of Scotland. Issue 3 (6th January 2017) - Radley, Andrew; Melville, Karen; Tait, Jan; Stephens, Brian; Evans, Josie M M; Dillon, John F
Abstract : Objective: Comparison of uptake of dried blood spot testing (DBST) for hepatitis C virus (HCV) infection between community pharmacies and established services. Design: Quantitative evaluation of a service development with qualitative process evaluation undertaken in parallel. Setting: Six pharmacies from 36 community pharmacies within Dundee City, a large urban settlement with high levels of socioeconomic deprivation. Participants: Patients in receipt of opioid substitution therapy (OST) not tested for HCV within 12 months. The 6 pharmacies provided OST for approximately 363 patients from a cohort of 1385 patients within Dundee City. Intervention: Provision of DBST by pharmacists. Main outcome measure: Receipt of DBST between January and December 2014. Results: 43 of 143 service users with no record of testing from the 6 community pharmacies accepted DBST. Of 561 from the remaining 1022 service users with no record of testing, 75 were tested for HCV (30% vs 13%). The OR for increased uptake of testing within the 6 pharmacies was 2.25 (95% CI 1.48 to 3.41, Z statistic=3.81, p=<0.0001) compared with other services. The DBST taken by the pharmacies provided 12 patients with a reactive test. The process evaluation identified key themes important to staff and recipients of the service. A logic model was constructed. Limitations: Non-experimental service evaluation performed in community pharmacies records service activity in one location across a single time period. Interpretation: Some evidence that DBST from community pharmacies may be feasible. Service users received the service positively. Staff reported that DBST was straightforward and achievable.